PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING DENGAN PENDEKATAN CULTURALLY RESPONSIVE TEACHING UNTUK MENINGKATKAN HASIL BELAJAR PENDIDIKAN PANCASILA SISWA KELAS III B SDN 4 PALANGKA - Emmy Mudiarti; Abd. Rahman Azahari; Roso Sugiyanto; Ichyatul Afrom (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This classroom action research was conducted to improve student learning outcomes in the subject of Pancasila Education by implementing the Problem-Based Learning (PBL) model combined with the Culturally Responsive Teaching (CRT) approach. The study involved 13 third-grade students at SDN 4 Palangka during the even semester of the 2024/2025 academic year. The research was conducted in two cycles, with each cycle consisting of one meeting. The learning process was carried out using the PBL model that emphasizes problem-solving and was integrated with the CRT approach, which respects students' cultural backgrounds to make learning more contextual and meaningful. The research data were collected through observation, documentation, and tests administered at the end of each cycle. The results of the pre-cycle showed a class average score of 52.30, with only 30.77% of students achieving the minimum mastery criteria (KKM). In Cycle I, the class average increased to 70.76 with 69.23% mastery. In Cycle II, there was a significant improvement with an average score of 90.00 and 84.61% of students achieving mastery. These findings indicate that the application of the PBL model combined with the CRT approach effectively enhances students’ learning outcomes in Pancasila Education.